A slack arrival strategy to promote flex-route transit services. (July 2018) - Zheng, Yue; Li, Wenquan; Qiu, Feng
Highlights: Theoretical and simulation models are developed to reproduce transit operation. The system performance is evaluated under expected and unexpected demand levels. A slack arrival strategy is proposed to reduce rejected requests and idle time. Experiments show that the slack arrival strategy can improve the system performance by up to 40%. Abstract: Flex-route transit, which combines the advantages of fixed-route transit and demand-responsive transit, is one of the most promising options in low-demand areas. This paper proposes a slack arrival strategy to reduce the number of rejected passengers and idle time at checkpoints resulting from uncertain travel demand. This strategy relaxes the departure time constraints of the checkpoints that do not function as transfer stations. A system cost function that includes the vehicle operation cost and customer cost is defined to measure system performance. Theoretical and simulation models are constructed to test the benefits of implementing the slack arrival strategy in flex-route transit under expected and unexpected demand levels. Experiments over a real-life flex-route transit service show that the proposed slack arrival strategy could improve the system performance by up to 40% with no additional operating cost. The results demonstrate that the proposed strategy can help transit operators provide more cost-efficient flex-route transit services in suburban and rural areas.